THE SIMULATION OF EGG NUMBER OF AEDES AEGYPTI USING STAGE-STRUCTURED MATRIX MODEL - Tokachil, Najir; Yusoff, Nuraini; Yahya, Abdullah (Journal of Technology Management and Business, 2018)
The distribution of rainfall is one of the factors which contribute to the development of Aedes aegypti life cycle. The fluctuation of rainfall might influence the acceleration of Aedes aegypti growth and at same time influence the increase of dengue cases. Many types of mosquitoes strictly need water to lay their eggs therefore in this research, the egg number of Aedes aegypti mosquito was simulated by using stage-structured matrix model. The development of egg numbers were associated with rainfall distribution and mosquito life cycle which consist of egg, larva, pupa, and adult. A stage-structured Lefkovitch matrix model was used for the simulation. An egg hatching function depends on rainfall was one significant parameter rate of matrix model which affect the whole mosquito life cycle. The graphical results were shown to illustrate the relationship between the rainfall and egg number. We found that there was a significant relation between the rainfall, and egg number. However, it is recommended to look for more possible factors such as size of opening container, humidity and temperature which contribute to the development of mosquito in order to acquire more accurate results.